Electronic structure of magnetic Fe/MgO/Fe/Co multilayer structure by NEXAFS spectroscopy. (April 2017) - Singh, Jitendra Pal; Gautam, Sanjeev; Lim, Weon Cheol; Asokan, K.; Singh, Braj Bhusan; Raju, M.; Chaudhary, Sujeet; Kabiraj, D.; Kanjilal, D.; Lee, Jenn-Min; Chen, Jing-Ming; Chae, Keun Hwa
Abstract: The present work investigates the local electronic structure of magnetic Fe/MgO/Fe/Co multilayer structure by using angle dependent near-edge X-ray absorption fine structure (NEXAFS) spectroscopy. The multilayer stack was grown on Si(100) substrates using electron-beam evaporation. X-ray diffraction study reveals the polycrystalline nature of different layers in the stack. Transmission electron microscopy shows different layers separated with each other except for upper Fe and Co layers. Magnetic nature of deposited structure was confirmed using vibration sample magnetometer. While the Fe L -edge NEXAFS measurements with total electron yield mode exhibit the spectral features that are indicative for formation of FeOx, the total fluorescence yield mode measurements exhibit onset of metallic nature of the Fe layer. These measurements at the Co L -edge reflect the presence of metallic nature of cobalt. Mg K -edge measurements performed at different angles exhibit local electronic structure of MgO layers very much similar to that of bulk MgO. Further, O K -edge fine structure supports the results obtained from various edges for the elements in each layer. Highlights: Deposition of Fe/MgO/Fe/Co stack by e-beam evaporation. Fe presents in oxidized as well as in metallic form. Co shows metallic nature.